(untitled) (ModaPalavra e-periódico, 2014)
The article discusses how the monograms are used as symbols of singling out individuals, when placed in a certain context. It is about a bibliographic and descriptive research, based on the identification of a collection of clothing found in the State University of Santa Catarina’s Modateca, which bears the monogram EH. It was through research of literature and based on surveys of historical information, that the monograms were studied and identified, as well as their origins and evolution, noting that they were originated in antiquity and evolved to the present day, adapting to the reality of each decade. Due to research directly based on the collection, it was concluded that it was to Elizabeth Hauer that the monogram EH belonged, which is the essence of this article.